All sprayed fluorine-free membrane electrode assembly for low-platinum and low-humidity proton exchange membrane fuel cells. Issue 16 (11th April 2023) - Yu, Weisheng; Yang, Xiaoqi; Liang, Xian; Xu, Yan; Shen, Xianhe; Ge, Xiaolin; Wu, Liang; Xu, Tongwen
Abstract : We propose an all-sprayed fluorine-free membrane electrode assembly for low-platinum and low-humidity proton exchange membrane fuel cell application. Abstract : Reducing the platinum catalyst loading and humidity dependence of membrane electrode assemblies (MEAs) is highly desirable for commercializing proton exchange membrane fuel cells (PEMFCs). Meanwhile, replacing the perfluorinated sulfonic-acid PEMs with fluorine-free hydrocarbon membranes can reduce manufacturing costs. We present an all spraying (AS) method to fabricate a fluorine-free hydrocarbon-based MEA (AS-MEA). Such an MEA achieves a much higher H2 /O2 fuel cell performance than the conventional catalyst-coated substrate MEA (CCS-MEA). The peak power density is 1.6 W cm −2 for the AS-MEA vs. 1.2 W cm −2 for the CCS-MEA with 100% relative humidity (RH) and 0.1/0.1 L per min H2 /O2 and 0.1 MPa backpressure gas feeds. More importantly, the performance superiority is particularly prominent at low RH and catalyst loading. The AS-MEA achieves a competitive peak power density of 0.6 W cm −2 at 40% RH with a low Pt loading of 0.1 mg cm −2, which is more than 3-fold that of the CCS-MEA. Equivalent-circuits-based analyses of electrochemical impedance spectroscopy show that the exceptional performance arises from the tightly integrated PEM–catalyst layer boundary, as confirmed by the cross-sectional morphological investigations. Moreover, the AS-MEA shows appreciable in situ durability during a 100 h accelerated stress test.